An analysis of industry regimes synchronization in the eurozone - Dias, J. G.; Ramos, S. (JCMS: Journal of Common Market Studies, 2015)
Geographical versus industrial diversification has been the subject of much debate in equity investment strategies. This article revisits this issue and analyzes the contention that if national factors have lost importance since the launch of the euro, then the regime dynamics of industry indexes in the eurozone countries should be more similar. Results show a core group of country-industry indexes sharing the same regime dynamics, which comprise the majority of industry indexes of France and Germany. After the euro launch, a group of industry indexes gained more similarities with the core group of the eurozone – notably industries from Italy, Spain and Finland. Nevertheless, dynamics in a small group of industries did not change. Overall, synchronization between country-industry indexes has increased except for a small group of industries.